The patient perspective on sirolimus for epithelioid hemangioendothelioma (EHE): results of a community survey highlighting the importance of equitable access to treatments - Robinson, Denise; Leonard, Hugh; Baldi, Giacomo Giulio; Tap, William D.; Jones, Robin L.; Stacchiotti, Silvia; Pantziarka, Pan (Frontiers in Oncology, 2024)
Background Epithelioid hemangioendothelioma (EHE) is an ultra-rare, vascular sarcoma with clinical presentation ranging from an indolent to an aggressive form. Over 50% of patients present with metastatic disease, requiring systemic therapy, although no systemic therapies are specifically approved for EHE. Retrospective evidence supports the activity of mTOR inhibitors (e.g. sirolimus), although available only off-label. EHE patients and advocates are therefore working to support approval of effective treatments by collecting data on patient perspectives and experiences. Materials and Methods In February 2023, the EHE Rare Cancer Charity (UK) and The EHE Foundation (US), with other advocates, conducted a survey of perspectives and experiences of EHE patients regarding the use and accessibility of sirolimus. The survey consisted of 20 questions designed for individuals undergoing treatment, those who had been treated, or had never been treated with the drug. Widely promoted within the patient community, the online survey categorized patients into three cohorts for the analysis: liver transplant patients, non-transplant patients who had ever taken sirolimus and sirolimus-naïve non-transplant patients. Results The survey evaluated data from 129 patient responses from 21 countries, mostly from USA, UK, Australia, and Canada (70%). The liver transplant, sirolimus and non-sirolimus cohorts were 16%, 25% and 59%, respectively. In the sirolimus group 66% reported treatment durations exceeding one year, with 16% exceeding five years, indicating the drug’s efficacy. In the non-sirolimus group, the drug was not available for 42% and for 11% sirolimus was available but not selected for treatment because of its off-label status. Overall, 87% of all patients across all cohorts expressed the importance of the drug’s availability as hugely or very important. Conclusion The survey responses highlight the activity of sirolimus for EHE and the importance of securing a label extension for the drug delivering equitable access to this treatment for patients.